Odessa recollected : the port and the people - Herlihy, Patricia; Harvard Ukrainian Research Institute (Boston : Ukrainian Research Institute, Harvard University ; Brighton, MA : Academic Studies Press, 2018)
The present book brings together--indeed, re-collects--some of the most valuable and thought-provoking research on Odessa and its culture, community, and economy published by Patricia Herlihy over several decades of her work. Scholars of Ukraine, Russia, and the former Soviet Union will find in this book a helpful resource for their research and teaching.
Frontmatter -- Table of Contents -- Acknowledgments -- Introduction -- Part One. Culture -- CHAPTER 1. The Persuasive Power of the Odessa Myth -- CHAPTER 2. Odessa Memories -- CHAPTER 3. How Ukrainian Is Odesa? From Odessa to Odesa -- CHAPTER 4. Jewish Writers of Odessa 1800-1940 -- Part Two. Community -- CHAPTER 5. Death in Odessa: A Study of Population Movements in a Nineteenth-Century City -- CHAPTER 6. The Ethnic Composition of the City of Odessa in the Nineteenth Century -- CHAPTER 7. Greek Merchants in Odessa in the Nineteenth Century -- CHAPTER 8. The Greek Community in Odessa, 1861-1917 -- Part Three. Commerce -- CHAPTER 9. Odessa: Staple Trade and Urbanization in New Russia -- CHAPTER 10. Commerce and Architecture in Odessa in Late Imperial Russia -- CHAPTER 11. Port Jews of Odessa and Trieste -- A Tale of Two Cities -- CHAPTER 12. Russian Wheat and the Port of Livorno 1794-1865 -- CHAPTER 13. South Ukraine as an Economic Region in the Nineteenth Century -- Index
In English.
Includes bibliographical references and index.
Online resource; title from PDF title page (ProQuest, viewed February 13, 2025).
JSTOR
Keywords: Odesa (Ukraine) -- History; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; HISTORY / Europe / Eastern; Ukraine -- Odesa; Odessa; Russian Empire; Soviet Union; Ukraine; Ukrainian commerce; Ukrainian culture; History